Stanley Hauerwas' Theological Ethics in Eschatological Perspective - Wells, Samuel (Scottish journal of theology, 2000)
The three most common criticisms of Stanley Hauerwas' work are that he is a sectarian, that he is a fideist, and that he lacks a doctrine of creation. My intention in this essay is to show that how greater attention to the eschatological implications of his theological ethics would enable Hauerwas successfully to respond to his critics.